Mural 3D dan Boneka Pagar Kreatif Berbasis Biofilik untuk Pelatihan Olah Media Belajar KKG PAUD Gugus V Loa Janan: Biophilic-Based 3D Mural and Creative Fence Dolls for Training in Educational Media Development at the PAUD Teacher Working Group Cluster V Loa Janan - Cisyulia Octavia HS; Andi Farid Hidayanto; Dian Dwi Nur Rahmah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Early Childhood Education (PAUD) provides a critical foundation for child development from birth through entry into primary school. In Loa Janan District, Kutai Kartanegara Regency, there are 43 PAUD institutions with 1,481 students and 126 teachers. Needs analysis revealed that the PAUD Teacher Working Group (KKG) Cluster V, comprising 9 schools with 325 students and 39 teachers, faces challenges including limited facilities, insufficient government support, conventional teaching methods, limited understanding of the greenship concept, and restricted access to training. This community service program aimed to introduce greenship innovation into educational media development through the use of sustainable materials and biophilic approaches, while providing hands-on training for teachers at TK A’Sidiq and TK Bina Anaprasa Melati, serving as training centers. The methods included socialization, participatory workshops, direct application of 3D mural and creative fence doll technologies, and continuous mentoring and evaluation. The results demonstrated significant improvement in teacher creativity, enabling them to design biophilic-based educational play media and apply interactive two-way learning with students. Teachers also acquired additional competencies to serve as instructors in other clusters, thereby enhancing both professional capacity and economic welfare. In conclusion, the program effectively strengthened teacher competencies in sustainable and innovative media development, aligned with Asta Cita, the Sustainable Development Goals (SDGs), Key Performance Indicators (IKU), and the National Research Master Plan (RIRN). Evaluation through questionnaires and observation confirmed a shift from one-way teaching to dynamic, collaborative learning, ensuring long-term sustainability and broader replication potential across other PAUD clusters.